Mental health literacy: evidence from adolescences in IRAN - Farzane Ahmadi; Farzaneh Karamitanha; Roya Karimi (International Journal of Adolescent Medicine and Health, 2026)
Abstract Objectives Mental health literacy (MHL) plays an important role in identifying mental illnesses. If MHL is low in a community, the identification and treatment of mental illnesses are delayed, ultimately jeopardizing individuals’ quality of life and well-being. Measuring health literacy levels in different regions and among various target groups is important. Methods In this cross-sectional study, all students enrolled across three majors – medicine, dentistry, and pharmacy – were surveyed (n=296). Data were collected on variables including age, gender, marital status, place of residence, parents’ education level, and students’ MHL, which was measured by the Mental Health Literacy Scale (MHLS). Results The level of MHL was moderate to high, with mean 90.80 ± 7.89. The level of MHL was significantly higher among students whose parents did not have a university education and in students who lived in dormitories. Conclusions In our study, overall mental health literacy was moderate to high, but knowledge of the professional help available was insufficient, highlighting the need for active mental health education in schools, universities, and communities, and urging policymakers to prioritize this issue in health programs.